Development of Multifunctional Magnetic Nanoparticles for Genetic Engineering and Tracking of Neural Stem Cells. Issue 7 (11th February 2016) - Adams, Christopher; Israel, Liron Limor; Ostrovsky, Stella; Taylor, Arthur; Poptani, Harish; Lellouche, Jean‐Paul; Chari, Divya
Abstract : Genetic modification of cell transplant populations and cell tracking ability are key underpinnings for effective cell therapies. Current strategies to achieve these goals utilize methods which are unsuitable for clinical translation because of related safety issues, and multiple protocol steps adding to cost and complexity. Multifunctional magnetic nanoparticles (MNPs) offering dual mode gene delivery and imaging contrast capacity offer a valuable tool in this context. Despite their key benefits, there is a critical lack of neurocompatible and multifunctional particles described for use with transplant populations for neurological applications. Here, a systematic screen of MNPs (using a core shown to cause contrast in magnetic resonance imaging (MRI)) bearing various surface chemistries (polyethylenimine (PEI) and oxidized PEI and hybrids of oxidized PEI/alginic acid, PEI/chitosan and PEI/polyamidoamine) is performed to test their ability to genetically engineer neural stem cells (NSCs; a cell population of high clinical relevance for central nervous system disorders). It is demonstrated that gene delivery to NSCs can be safely achieved using two of the developed formulations (PEI and oxPEI/alginic acid) when used in conjunction with oscillating magnetofection technology. After transfection, intracellular particles can be detected by histological procedures with labeled cells displaying contrast in MRI (for real time cell tracking). Abstract : Multifunctional magnetic nanoparticles can mediate combinatorial therapy, providing a platform for simultaneous genetic engineering and imaging of transplant populations in facile, one‐step procedures. Using a systematic screen of nanoparticle surface chemistries, we show that particles with two coatings (polyethylenimine and a novel oxidized polyethylenimine/alginic acid combination) can safely deliver genetic material into neural stem cells whilst yielding contrast for magnetic resonance imaging.